The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.37201/req/099.2022
|View full text |Cite
|
Sign up to set email alerts
|

Microbial etiology of bacterial chronic prostatitis: systematic review

Abstract: Objectives. The importance of Gram-positive microorganisms and atypical bacteria in chronic bacterial prostatitis (CBP) has recently been described. For this reason, this study analyzes the etiology of CBP, as well as the evolution of antibiotic resistance through a systematic review. Material and methods. A systematic review of studies obtained through the MEDLINE (PubMed) database, related to the etiology and antibiotic resistance profile of CBP, published up July 1, 2021. Results. The most frequent isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…Para E. faecalis , las tasas de resistencia a nitrofurantoína y fosfomicina de Cai et al [ 10 ] concuerdan con lo hallado en nuestro trabajo. Si bien con fosfomicina no existe una amplia experiencia clínica y nitrofurantoina se ha empleado como terapia de continuación, para erradicar la bacteriuria que frecuentemente se asocia a la BPS [ 19 ].…”
Section: Discussionunclassified
“…Para E. faecalis , las tasas de resistencia a nitrofurantoína y fosfomicina de Cai et al [ 10 ] concuerdan con lo hallado en nuestro trabajo. Si bien con fosfomicina no existe una amplia experiencia clínica y nitrofurantoina se ha empleado como terapia de continuación, para erradicar la bacteriuria que frecuentemente se asocia a la BPS [ 19 ].…”
Section: Discussionunclassified
“…Recent studies have shown an evolution in the treatment options for CBP. Though fluoroquinolones have been the antibiotic of choice for the treatment of CBP, the emerging bacterial resistance amongst common uropathogens like E. coli , Enterococcus faecalis and Staphylococcus spp., and persistence or recurrences of infection have brought forth other, more unconventional treatments for treating CBP ( Mendoza-Rodríguez, et al, 2023 ). This includes utilising drugs like Fosfomycin which have traditionally been used for treatment of uncomplicated urinary tract infections, as well as alternative modalities like phage therapy ( Letkiewicz, et al, 2010 ; Su, et al, 2020 ; Xiong, et al, 2020 ; Marino, et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…While several risk factors for progression to chronic bacterial prostatitis (CBP) have been identified—such as alcohol abuse, diabetes mellitus, large prostate volume and history of prostate surgery [ 11 ]—most of the patients with ABP who progress to CBP do not present known risk factors of progression. Gram-positive bacteria and atypical bacteria are the main pathogens involved in the etiology of CBP, with Enterococcus faecalis (46.90%), Staphylococcus (22.30%), Escherichia coli (15.09%) and atypical bacteria (6.04%) being the more prevalent [ 12 ].…”
Section: Introductionmentioning
confidence: 99%